Will Sirtuins Be Promising Therapeutic Targets for TBI and Associated Neurodegenerative Diseases? - Yang, Qianjie; Zhou, Yunxiang; Sun, Yuting; Luo, Yi; Shen, Ye; Shao, Anwen (Frontiers in Neuroscience, 2020)
Traumatic brain injury (TBI), a leading cause of morbidity worldwide, induces mechanical, persistent structural and metabolic abnormalities in neurons and other brain-resident cells. The key pathological features of TBI include neuroinflammation, oxidative stress, excitotoxicity, and mitochondrial dysfunction. These pathological processes persist for a period of time after TBIs. Sirtuins are evolutionarily conserved nicotinamide-adenine dinucleotide (NAD+)-dependent deacetylases and mono-ADP-ribosyl transferases. The mammalian sirtuin family has seven members, referred to as Sirtuin (SIRT) 1–7. Accumulating evidence suggests that SIRT1 and SIRT3 play a neuroprotective role in TBI. Although the evidence is scant, considering the involvement of SIRT2, 4-7 in other brain injury models, they may also intervene in similar pathophysiology in TBI. Neurodegenerative diseases are generally accepted sequelae of TBI. It was found that TBI and neurodegenerative diseases have many similarities and overlaps in pathological features. Besides, sirtuins play some unique roles in some neurodegenerative diseases. Therefore, we propose that sirtuins might be a promising therapeutic target for both TBI and associated neurodegenerative diseases. In this paper, we review the neuroprotective effects of sirtuins on TBI as well as related neurodegeneration and discuss the therapeutic potential of sirtuin modulators.